PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV SD NEGERI 012 PAGARAN TAPAH DARUSSALAM - Lisna Hutabarat (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This research is motivated by the lack of civics learning outcomes third grade students SD Negeri 012 Pagaran Tapah Darussalam. This study aims to improve learning outcomes civics through the implementation of cooperative learning model scramble technique grade IV in SD Negeri 012 Pagaran Tapah Darussalam, held for 1 month. Subjects in the study were students of class IV in SD Negeri 012 Pagaran Tapah Darussalam in the school year 2014/2015 the number of students as many as 21 people, consisting of 8 male students and 13 female students. Forms of research is classroom action research. The research instrument consists of instruments and instrument performance data collecting activity observation sheet teachers and student activities. Based on the results of this study concluded that the implementation of cooperative learning model scramble technique can improve improve learning outcomes civics fourth grade students in SD Negeri 012 Pagaran Tapah Darussalam. This success is due to the use of cooperative learning activity scramble engineering students become more active, which means the activity of students with more positive following the learning process provided by the teacher and in discussions within and between groups. Under these conditions, the enrollment rate will increase and ultimately improve learning results. In the first cycle of research results show that students who have not reached the minimum completeness criteria (KKM) of 8 students or 38.1%. The number of students who scored first classical completeness in cycle consists of 13 people or 61.9%, while in the second cycle increased to 21 people or 100%. This situation shows that the improvement of learning in civics using cooperative learning model scramble technique can be said to be successful. Improved learning outcomes in the second cycle also seen that there are no more students who have not reached the minimum completeness criteria (KKM), completeness class increased from 61.9% to 100%.